The effect of health education based on the health belief model using flashcards on anxiety and perception of breast cancer risk in adolescent girls - Leonita, Ni Nyoman Ratih; Lisnawati, Ketut; Citrawati, Ni Ketut (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Early detection of breast cancer is an important effort in reducing morbidity and mortality in women, however, awareness and practice of breast self-examination (SADARI) among adolescent girls are still relatively low, potentially causing delayed detection in adulthood. The lack of systematic health education and engaging learning methods are the main factors in the low early detection behavior in this age group. Purpose: To determine the effect of health education based on the Health Belief Model (HBM) with flashcard media on early detection of breast cancer in adolescent girls. Method: The study used a one-group pretest–posttest design with a sample of 34 12th-grade female students of SMA Negeri 2 Abiansemal selected using a purposive sampling technique. Results: Univariate analysis showed that before the intervention, most respondents were in the sufficient action category with an average score of 64.61, whereas after being given HBM-based health education with flashcard media, there was an increase in early detection actions to the good category with an average score of 84.19. Bivariate analysis using the Wilcoxon test showed a significant difference between early detection measures before and after the intervention with a p value = 0.000 (p < 0.05), which indicates that HBM-based health education with flashcard media has a significant effect on increasing early detection measures for breast cancer. Conclusion: These results indicate that the HBM approach combined with interactive visual media is able to in crease adolescents' perceptions of risks, benefits, and self-confidence in performing BSE, so that health education with this method is effective and relevant to be implemented as a promotive and preventive strategy in the school environment from adolescence. Keywords: Early Breast Cancer Detection; Flashcards; Health Belief Model.